Faith, Family, and Fear: A Triangular Analysis of Academic Stress and Suicidal Ideation among Muslim Students in Pakistani Universities - Muhammad Umair Farooq; Dr. Saifullah; Abid Hussain (Social Science Review Archives, 2025)
This study explores the intricate interplay of faith, family, and fear in shaping the experiences of academic stress and suicidal ideation among Muslim students. Through qualitative interviews, the research uncovers how these three dimensions form a dynamic, interconnected triangle that both protects and endangers students’ mental health. Faith emerges as a double-edged sword, offering hope and resilience for some while generating guilt and internal conflict for others. Family serves as both a source of support and a significant source of pressure, with high expectations and limited openness around emotional struggles contributing to students’ sense of isolation. Fear of failure, judgment, and divine punishment acts as a powerful barrier to help-seeking, perpetuating silence and hidden suffering. The findings highlight the urgent need for faith-sensitive, culturally informed mental health interventions within academic settings. Recommendations include training educators and counselors in religious and cultural literacy, engaging faith leaders to de-stigmatize mental health, and establishing peer support groups to foster open dialogue. By addressing the unique intersection of faith, family, and fear, this research advocates for holistic, contextually grounded strategies to promote psychological well-being and reduce suicide risk among Muslim youth